Schematic proposal of spatial exclusion. Case Monterrey, Mexico - Padilla Herrera, Diana (Universidad de Boyacá, 2020)
The maps, as a mean of graphic representation, show only one reality of the city, as schemes that integrate urban structures, but in turn, hide others. Exclusion –from a territorial point of view– undergoes unnoticed by social dynamics, so recovering the territoriality becomes fundamental. This article proposes a new schematization around exclusion, where the concept of spatial exclusion is developed, which allows the identification of spatial processes that produce exclusion. So, in the city exists multiple forces that are not identified; therefore, the schematization of spatial exclusion becomes an alternative of graphing to make visible the forces that interact in the built environment. This raises new possibilities of approaching the spatial phenomena of contemporary cities.